Monolayer Tungsten Disulfide (WS2) via Chlorine‐Driven Chemical Vapor Transport. Issue 33 (10th July 2017) - Modtland, Brian J.; Navarro‐Moratalla, Efren; Ji, Xiang; Baldo, Marc; Kong, Jing
Abstract : Large‐scale production of high‐quality tungsten disulfide (WS2 ) monolayers is a prerequisite for potential device applications using this promising transition metal dichalcogenide semiconductor. The most researched technique is chemical vapor deposition, typically involving the reaction of sulfur vapors with tungsten oxide. Other techniques such as physical vapor deposition have been explored with some success, but low vapor pressures make growth difficult. This study demonstrates a growth process that relies on halide‐driven vapor transport commonly utilized in bulk crystal growth. Using a small amount of sodium chloride salt as a source of chlorine, nonvolatile WS2 can react to form gaseous tungsten chloride and sulfur. With an open tube system, a controlled reaction generates mono and few‐layer WS2 crystals. Optical and physical characterization of the monolayer material shows good uniformity and triangular domains over 50 µm in length. Photoluminescence transient measurements show similar nonlinear exciton dynamics as exfoliated flakes, attributed to multiparticle physics. Requiring only the powder of the desired crystal and appropriate halide salt as precursors, the technique has the potential to realize other layered materials that are challenging to grow with current processes. Abstract : A method for growing high‐quality monolayer transition metal dichalcogenides (TMDs) using chemical vapor transport in an open‐tube system is presented. Selecting tungsten disulfide (WS2 ) as a model TMD, sodium chloride salt is demonstrated as a transport agent to synthesize monolayer crystals with excitonic properties comparable to exfoliated samples.